2020
DOI: 10.1200/jop.19.00328
|View full text |Cite
|
Sign up to set email alerts
|

Opportunity Costs of Receiving Palliative Chemotherapy for Metastatic Pancreatic Ductal Adenocarcinoma

Abstract: PURPOSE: The median overall survival (OS) for metastatic pancreatic ductal adenocarcinoma (mPDAC) is < 1 year. Factors that contribute to quality of life during treatment are critical to quantify. One factor—time spent obtaining clinical services—is understudied. We quantified total outpatient time among patients with mPDAC receiving palliative systemic chemotherapy. METHODS: We conducted a retrospective analysis using four patient-level time measures calculated from the medical record of patients with mPDA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 18 publications
0
52
1
Order By: Relevance
“…Cancer care‐related time was calculated using data from all three sources (Figure 1). 11 Ambulatory care time, or time spent on routine care, was calculated using the following equation:Average total ambulatory care time=(Average time spent traveling to and from clinicsurvey×Lab rateclaims)+(Average non-clinic visit infusion timedirect observation×Infusion rateclaims)+(Average clinic visit timedirect observation×Clinic visit rateclaims)+(Average lab timedirect observation×Lab rateclaims)+(Average CT scan timedirect observation×CT scan rateclaims)+(Average bone scan timedirect observation×Bone scan rateclaims).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cancer care‐related time was calculated using data from all three sources (Figure 1). 11 Ambulatory care time, or time spent on routine care, was calculated using the following equation:Average total ambulatory care time=(Average time spent traveling to and from clinicsurvey×Lab rateclaims)+(Average non-clinic visit infusion timedirect observation×Infusion rateclaims)+(Average clinic visit timedirect observation×Clinic visit rateclaims)+(Average lab timedirect observation×Lab rateclaims)+(Average CT scan timedirect observation×CT scan rateclaims)+(Average bone scan timedirect observation×Bone scan rateclaims).…”
Section: Methodsmentioning
confidence: 99%
“…Cancer care-related time was calculated using data from all three sources ( Figure 1). 11 Ambulatory care time, or time spent on routine care, was calculated using the following equation:…”
Section: Outcome: Patient Health Care Timementioning
confidence: 99%
“…A retrospective analysis recently suggested that palliative systemic cancer therapy accounted for approximately 10% of the survival time awake remaining to pancreatic cancer patients with distant metastases. 1 Telemedicine applications can facilitate patient access to specialised healthcare from remote and may therefore be ideally suited for the medical oncology setting. With the recent SARS-CoV-2 pandemic the need for…”
Section: Introductionmentioning
confidence: 99%
“…A retrospective analysis recently suggested that palliative systemic cancer therapy accounted for approximately 10% of the survival time awake remaining to pancreatic cancer patients with distant metastases. 1 …”
Section: Introductionmentioning
confidence: 99%
“…Patients may spend a significant amount of time obtaining clinical services. One study demonstrated that over half of clinical visits were spent on commuting and waiting for care [ 17 ]. Time between treatment modalities may be spent on the preparation and planning of the next phase of therapy.…”
Section: Discussionmentioning
confidence: 99%